Effect of E-glass fibers addition on compressive strength, flexural strength, hardness, and solubility of glass ionomer based cement - Tamer M. Hamdy (BMC, 2024)
Abstract Background In dentistry, glass-ionomer cements (GICs) are extensively used for a range of applications. The unique properties of GIC include fluoride ion release and recharge, chemical bonding to the tooth's hard tissues, biocompatibility, a thermal expansion coefficient like that of enamel and dentin, and acceptable aesthetics. Their high solubility and poor mechanical qualities are among their limitations. E-glass fibers are generally utilized to reinforce the polymer matrix and are identified by their higher silica content. Objectives The purpose of the study was to assess the impact of adding (10 wt% and 20 wt%) silane-treated E-glass fibers to traditional GIC on its mechanical properties (compressive strength, flexural strength, and surface hardness) and solubility. Methods The characterization of the E-glass fiber fillers was achieved by XRF, SEM, and PSD. The specimens were prepared by adding the E-glass fiber fillers to the traditional GIC at 10% and 20% by weight, forming two innovative groups, and compared with the unmodified GIC (control group). The physical properties (film thickness and initial setting time) were examined to confirm operability after mixing. The evaluation of the reinforced GIC was performed by assessing the compressive strength, flexural strength, hardness, and solubility (n = 10 specimens per test). A one-way ANOVA and Tukey tests were performed for statistical analysis (p ≤ 0.05). Results The traditional GIC showed the least compressive strength, flexural strength, hardness, and highest solubility. While the GIC reinforced with 20 wt% E-glass fibers showed the highest compressive strength, flexural strength, hardness, and least solubility. Meanwhile, GIC reinforced with 10 wt% showed intermediate results (P ≤ 0.05). Conclusion Using 20 wt% E-glass fiber as a filler with the traditional GIC provides a strengthening effect and reduced solubility.